Cartografia do processo de pesquisa com estudantes pesquisadores de escola pública: m(p)aternidade na adolescência em cena - Gonçalves, Shirley Dias (2023)
This research aims to map the research process with adolescent researchers from a state public school located in Fortaleza-CE on maternity and paternity in adolescence in the school routine. The following question is analyzed: How can the production of a cartography with adolescents from a state public school in Fortaleza about maternity and paternity in adolescence be constituted as a device in research WITH adolescents? The theoretical-methodological principles are from intervention research (IP) - especially the cartography of Deleuze and Guattari (1995) and from French Institutional Analysis (Lourau, 1993; 2004). The relevance of the research consists in analyzing the research process WITH adolescents on the theme m(p)aternity within the territory of the public school and not ABOUT adolescents. In the first moment, entitled between screening and touch (Kastrup, 2008), we followed an extension course "Training of young researchers in everyday school life" which, among other topics, mobilized the theme of adolescent motherhood and fatherhood. In the second moment, entitled landing, we had the support of the Institutional Program of Scientific Initiation Scholarships for High School (PIBIC-EM), of the National Council for Scientific and Technological Development (CNPq), which offered conditions of possibilities to create a research device. In this one year, a group of researchers made up of three high school students (two PIBIC-EM scholarship holders and one volunteer), undergraduate and graduate students of Psychology at the Federal University of Ceará (UFC) collectively carried out a research, remotely due to the context of the Covid-19 pandemic. The PIBIC-EM students participated as protagonists of the entire process of collective construction of the research, from planning to its execution, acting in the construction and delimitation of the object, starting question, objectives, creation and application of the investigation instrument (online form), the collective analysis of the data and the restitution of the results, with the elaboration of a digital booklet. The online questionnaire consisted of 27 questions, comprised of multiple-choice and subjective questions, and was answered by 599 people (84.11% students, 6.52% former students, 4.01% mothers/fathers/guardians, 3.68% teachers, 1.90% management, 0.7% employees). This research also discusses the relationship between gender, motherhood and fatherhood. The power of the participation of high school adolescents can be considered when developing a survey with the reach of various segments of the school community and which counted on the partnership and mobilization of the Potencia school, involving teachers and managers even in such an adverse period of remote context due to the pandemic. The collective, formed by high school researchers from PIBIC-EM and academic researchers from UFC, functioned as a learning community (bell hooks, 2021), with a desire to learn, feel, affect, implicate, and invent through experimentation in this research process.